Evaluating the Influence of Chain Branching on the Adhesion Strength between Layers in Fused Deposition Modeling - Alturkestany, Mohammed (My University, 2017)
Fused deposition modeling (FDM) is gaining an ever increasing attention for its ability to fabricate complex geometry parts and prototypes at lower cost. The technology is striving to produce parts with high mechanical resistance that can withstand and perform under high stress environment. The adhesion strength between layers, transverse strength, is a limiting factor that need to be quantitatively evaluated to further understand and improve the bonding behavior of thermoplastic polymer in FDM. This interfacial adhesion is derived by the diffusion and penetration of polymer chains across the interface allowing the chain entanglement to form a bonding medium. This study investigates the bonding behaviour of polylactic acid (PLA) as a function of chain branching. The adhesion strength is quantitatively evaluated by developing and performing a peel test of a two-printed layer samples. It is possible to increase chain branching of PLA by bulk modification with epoxy chain extender. The modification of PLA was carried out using an internal batch mixer with four different concentrations of chain extender. The modified PLA was processed into print filament and characterized by parallel plate rheometry and DSC. It was found that the addition of chain extender increased molecular weight and degree of branching of PLA and in return the peel testing results reflected a significant increase in adhesion strength. Such improvement can be attributed to the long branched chains of PLA and its ability to create entanglements between layers. These findings can help in producing better PLA filaments to provide a higher stress resistance for FDM fabricated functional parts.
Keywords: 3D Printing; Additive Manufacturing; FDM; Fused Deposition Modeling; Adhesion; Bonding strength